2021
DOI: 10.3390/s21103415
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weather and Seasons on Falls and Physical Activity among Older Adults with Glaucoma: A Longitudinal Prospective Cohort Study

Abstract: Understanding periods of the year associated with higher risk for falling and less physical activity may guide fall prevention and activity promotion for older adults. We examined the relationship between weather and seasons on falls and physical activity in a three-year cohort of older adults with glaucoma. Participants recorded falls information via monthly calendars and participated in four one-week accelerometer trials (baseline and per study year). Across 240 participants, there were 406 falls recorded ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Best practices guidelines for planting street trees, and for ongoing tree maintenance, to minimize sidewalk damage have been published (MillionTreesNYC 2015 ; Mullaney et al 2015 ).Although sidewalk damage from street trees may increase risk for falls, the cooling effects of trees may prevent some falls. A study among individuals at high risk of falling found that higher temperatures were associated with significantly higher odds of a fall being injurious, as opposed to non-injurious (Vongsachang et al 2021 ). An ecologic study of Census blocks in Marin County CA found that a higher extent of tree canopy cover over streets was associated with lower rates of pedestrian falls among adults age 65 and older (Lee et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Best practices guidelines for planting street trees, and for ongoing tree maintenance, to minimize sidewalk damage have been published (MillionTreesNYC 2015 ; Mullaney et al 2015 ).Although sidewalk damage from street trees may increase risk for falls, the cooling effects of trees may prevent some falls. A study among individuals at high risk of falling found that higher temperatures were associated with significantly higher odds of a fall being injurious, as opposed to non-injurious (Vongsachang et al 2021 ). An ecologic study of Census blocks in Marin County CA found that a higher extent of tree canopy cover over streets was associated with lower rates of pedestrian falls among adults age 65 and older (Lee et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike indoor falls, which are more likely influenced by an individual's risk factors and health status, outdoor falls are often associated with health-promoting activities (e.g., walking, running, gardening) instead of poor health and are, in particular, substantially influenced by environmental factors, climate (e.g., winter weather, rain and extreme heat) and the physical aspects of the environment such as poorly maintained paving (Chippendale et al Kelsey et al 2012a , 2012b ; Li et al 2006 ; Satariano et al 20172017 ). While icy conditions are a known cause of outdoor falls, there is emerging evidence that injurious outdoor falls are also associated with higher temperatures (Lee et al 2022 ; Vongsachang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our findings indicate another environmental factor, seasonal effects, are also risk factors for activity limitations and participation restrictions and predict their changes of slopes within 1 year. Studies have indicated that seasonal changes are associated with specific circulatory disorders and limb weakness [ 54 ] and have varying physiological, psychological, and social function effects on patients over time [ 55 ]. Studies have revealed that environmental factors affect activity limitations and physical and mental impairment [ 56 ] and that participation restrictions in 65-year-olds are related to temperature, especially seasonal temperature changes from September to January [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounding factors including age, sex, total annual household income, Townsend deprivation index, smoking, alcohol drinking, education achievement, ethnic background, body mass index, allowance, and employment state at baseline were derived from questionnaires and interviews. As movement behaviors might also fluctuate remarkably among seasons, 25 the month of accelerometer tests was also included in this study. Considering the correlation between glaucoma and other diseases which might also affect movement behaviors, systemic comorbidities including diabetes, coronary heart disease, heart failure, stroke, hypertension, and cancer were identified based on questionnaires, interviews, and inpatient diagnosis records.…”
Section: Covariatesmentioning
confidence: 99%